Partial Ureteropelvic Junction Disruption after Blunt Trauma: Case Report - Jalal Eddine El Ammari; Youness Ahallal; Mohammed Jamal El Fassi; M. Hassan Farih (Case Reports in Urology)
Partial ureteropelvic junction disruption as a result of blunt trauma is rare and frequently missed by the initial trauma evaluation. Delays in diagnosis have also been associated with significant morbidity. A high index of suspicion should lead to appropriate investigations, and the management will be determined by the severity of the disruption. We present herein a 24-year-old man who was admitted to the Emergency Room with multiple organ injuries caused by a severe blunt trauma. Emergency celiotomy was performed for massive hemoperitoneum and shattered spleen which led to splenectomy. The diagnosis of partial UPJ disruption was missed preoperatively and suspected in CT scan after appearance of flank tender mass. Confirmation was obtained in retrograde ureteropyelography and treated conservatively with indwelling ureteral stent. We present herein an extensive review of the literature to examine the current status of this entity and to determine if improvements could be made in the diagnosis and treatment.